2020
DOI: 10.1186/s12944-019-1182-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of combination therapy with ezetimibe and statins versus a double dose of statin monotherapy in participants with hypercholesterolemia: a meta-analysis of literature

Abstract: Background: The aim of this study was to compare and summarize the lipid-altering effects of combination therapy with ezetimibe and statins (E/S) and a double dose of statin (D/S) monotherapy on patients with hypercholesterolemia. Methods: We conducted search on 2 medical databases, PubMed and EMBASE to identify all relevant studies. A meta-analysis was performed to clarify the efficacy in the two groups. Only double-blind Randomized controlled study (RCTs) of efficacy evaluation in the two groups with ezetimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 30 publications
2
83
1
2
Order By: Relevance
“…Furthermore, the current study found a higher prevalence of hypercholesterolemia among diabetic participants. A recently published Berlin Aging Study II (BASEII) found that elderly individuals on lipid lowering medication had a higher prevalence of diabetes [ 10 ]. However, most published studies have reported a higher prevalence of HC among diabetic individuals [ 27 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the current study found a higher prevalence of hypercholesterolemia among diabetic participants. A recently published Berlin Aging Study II (BASEII) found that elderly individuals on lipid lowering medication had a higher prevalence of diabetes [ 10 ]. However, most published studies have reported a higher prevalence of HC among diabetic individuals [ 27 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Age is also a strong risk factor for HC; more advanced age has been associated with higher risk of HC for both sexs [ 7 – 9 ]. In people who are in younger age groups (teenagers, young adults 18–25 years of age), HC can go undetected [ 10 ]. In a study by Basulaiman et al, it was reported that 65% of Saudis with HC were undiagnosed [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be supposed that the LEP receptor changes its expression following the stimulation of the increased plasma LEP since hormone local production was not changed. The increased LEPR expression observed in the Obese group suggests that the receptor plays a modulating role in the skin system control and that serum LEP may have a role in the pathogenesis of skin disease associated with obesity [ 61 ]. However, Arnold et al [ 62 ] have shown that among the different isoforms of LEPR (LEPRa, b, c, d, f: transmembrane), there is also a soluble form of the LEP receptor (LEPRe) capable of modulating the bio-availability and the consequent action of LEP.…”
Section: Discussionmentioning
confidence: 99%
“… 47 , 48 Therefore, inflammasome-mediated activation of caspase-1 and its target substrates are physiologically important to regulate immune cell response against microbial infections and metabolic activities. 32 , 49 However, infection resistance or obesity-associated chronic inflammation in peripheral tissues can lead to metabolic disturbances such as obesity, type two diabetes mellitus (T2DM), insulin resistance and cardiovascular diseases. 50 Chronic inflammation is usually associated with the release of oxidative metabolic intermediates like ROS, which in turn leads to organelle dysfunctions, including mitochondrial dysfunction.…”
Section: Caspase-1 Activation and Inflammationmentioning
confidence: 99%